2017
DOI: 10.1097/mib.0000000000001214
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors and Natural History of Disease Extension in Patients with Ulcerative Proctitis

Abstract: Background A proportion of patients with initial presentation of ulcerative proctitis (UP) progress to more extensive colitis. We sought to characterize the natural history and identify clinical predictors of extension in UP. Methods We performed a retrospective cohort study of participants with a new diagnosis of UP from January 2000 to December 2015. We used cox proportional hazard modeling to identify predictors of disease extension. Results Through December of 2015, we identified 169 cases of UP with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
(31 reference statements)
2
5
0
Order By: Relevance
“…BMI, endoscopic disease severity, appendectomy, and smoking are risk factors for the extension of UP according to previous results [10,13]. In our study, we found out that the severity of the disease is also correlated with the cumulative disease extension rate, which is consistent with previous research [13]. Besides, we also observed a higher extension rate in symptomatic patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…BMI, endoscopic disease severity, appendectomy, and smoking are risk factors for the extension of UP according to previous results [10,13]. In our study, we found out that the severity of the disease is also correlated with the cumulative disease extension rate, which is consistent with previous research [13]. Besides, we also observed a higher extension rate in symptomatic patients.…”
Section: Discussionsupporting
confidence: 92%
“…Risk factors of disease extension were also analyzed in previous studies [10,13]. BMI, endoscopic disease severity, appendectomy, and smoking are risk factors for the extension of UP according to previous results [10,13]. In our study, we found out that the severity of the disease is also correlated with the cumulative disease extension rate, which is consistent with previous research [13].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As an example, in the IBSEN cohort, 42% of patients with UP had proximal disease extension (28% to left-sided, 14% to extensive colitis) 31 . Meucci and colleagues reported that a more severe phenotype (recurrent flares, need for systemic steroids, or patients with chronically active disease), or lack of smoking were associated with progression of inflammation 11 , while in a different study appendectomy and obesity were associated with such a phenotype 32 . Our data indicate that two factors at the end of induction, including a high PUCAI score and lack of steroid-free clinical remission, were associated with progression.…”
Section: Discussionmentioning
confidence: 99%